Reactivation of simian immunodeficiency virus reservoirs in the brain of virally suppressed macaques. (2nd January 2017) - Gama, Lucio; Abreu, Celina M.; Shirk, Erin N.; Price, Sarah L.; Li, Ming; Laird, Greg M.; Pate, Kelly A. Metcalf; Wietgrefe, Stephen W.; O'Connor, Shelby L.; Pianowski, Luiz; Haase, Ashley T.; Van Lint, Carine; et al.
Abstract : Objective: Resting CD4 + T cells have been recognized as the major cell reservoir of latent HIV-1 during antiretroviral therapy (ART). Using an simian immunodeficiency virus (SIV)/macaque model for AIDS and HIV-related neurocognitive disorders we assessed the contribution of the brain to viral latency and reactivation. Design: Pigtailed macaques were dual inoculated with SIVDeltaB670 and SIV17E-Fr and treated with an efficacious central nervous system-penetrant ART. After 500 days of viral suppression animals were treated with two cycles of latency reversing agents and increases in viral transcripts were examined. Methods: Longitudinal plasma and cerebrospinal fluid (CSF) viral loads were analyzed by quantitative and digital droplet PCR. After necropsy, viral transcripts in organs were analyzed by PCR, in-situ hybridization, and phylogenetic genotyping based on env V1 loop sequences. Markers for neuronal damage and CSF activation were measured by ELISA. Results: Increases in activation markers and plasma and CSF viral loads were observed in one animal treated with latency reversing agents, despite ongoing ART. SIV transcripts were identified in occipital cortex macrophages by in-situ hybridization and CD68 + staining. The most abundant SIV genotype in CSF was unique and expanded independent from viruses found in the periphery. Conclusion: The central nervous system harbors latent SIV genomes after long-term viral suppression by ART, indicating that the brain represents a potential viral reservoir and should be seriously considered during AIDS cure strategies. Abstract : Supplemental Digital Content is available in the text